ESBL-Producing Escherichia coli from Cows Suffering Mastitis in China Contain Clinical Class 1 Integrons with CTX-M Linked to ISCR1 - Ali, Tariq; ur Rahman, Sadeeq; Zhang, Limei; Shahid, Muhammad; Zhang, Shiyao; Liu, Gang; Gao, Jian; Han, Bo (Frontiers in Microbiology, 2016)
Prevalence of pathogenic multi-drug resistant (MDR) extended-spectrum β-lactamase (ESBL)-producing Escherichia coli is rapidly increasing, becoming a global concern. In a veterinary context, ESBL-producing E. coli are mostly reported in poultry and pigs. Here, we report on the prevalence and characterize ESBL-producing E. coli isolated from diverse dairy farms in China. Overall, 36 (23.53%) out of 153 E. coli isolates from mastitic milk samples (n=1252) were confirmed as ESBL-producers by double-disc synergy testing and PCR. Nucleotide analysis of PCR amplicons revealed that blaCTX-M was the predominant ESBL gene detected in 28 (77.78%) isolates, with blaCTX-M-15 being the major (78.57%) allele encoding for ESBLs. Also, 22 (55.56%) and 6 (16.67%) of the ESBL isolates were carrying blaTEM and blaSHV genes, respectively, in singlet or in combination. The majority of these isolates belonged to phylo-group A (69.44%) and D (16.67%). Strikingly, all these isolates were found MDR reflecting high resistance (58-100%) to cephalosporins, including the fourth generation cefepime and non β-lactams. Additionally, class 1 integrons (intI1) were found in 30 (83.33%) isolates. Analysis of the integron 1 variable region encoding gene cassette indicated that they were carrying up to five different gene cassettes conferring resistance to various drugs with a predominant combination of dfrA17-aadA5 genes in tandem. However, no ESBL encoding genes were found in the cassettes. Interestingly, 22 (66.11%) of the ESBL isolates were also carrying insertion sequence common region 1 (ISCR1) which was found associated with most of the ESBL genes. Altogether, the current report on the high prevalence of ESBL-positive E. coli, particularly CTX-M-15, carrying integron 1 and ISCR1 elements are likely indicative of their rapid and wider dissemination, posing threats to veterinary and public health. To the best of our knowledge, this is the first comprehensive study to report on the alarming high occurrence of ESBL-producing E. coli from mastitic cows in China.